The department of truth complete conspiracy deluxe hc volume 1 ebook - Tynion IV, James (The Department of Truth (2020), 2023)
COLE TURNER has studied conspiracy theories all his life, but he isn’t prepared for what happens when he discovers that all of them are true, from the JFK Assassination to Flat Earth Theory and Reptilian Shapeshifters. One organization has been covering them up for generations. What is the deep, dark secret behind the Department of Truth?